The Correlation between Sleep Quality and Acne vulgaris Incidence in Medical Students of Universitas Tarumanagara - Helena Ivonne Cungse Adinegoro; Donatila Mano (Jurnal Kedokteran Diponegoro, 2024)
Background: Acne vulgaris is still occurred among medical students worldwide, with a prevalence range of 34,38% to 97,9%. Acne vulgaris, which affects the pilosebaceous unit, is suspected to be related to sleep quality because it involves many hormones, including melatonin, which is associated to sleep. Melatonin can suppress androgens, which play a crucial role in Acne vulgaris pathogenesis. Besides, some studies said that melatonin has a role to suppress inflammation. Medical students also often experience poor sleep quality. Previous studies on the correlation between sleep quality and Acne vulgaris have shown varied results. Objective: This research was conducted to confirm the correlation between sleep quality and Acne vulgaris. Methods: A total of 195 medical students from Tarumanagara University classes of 2021 and 2022 participated in this study by answering the Pittsburgh Sleep Quality Index (PSQI) and Acne vulgaris questionnaires. Samples were taken using non-random consecutive sampling. This research used an analytical observational method with a cross-sectional design. Results: The study found that 92 respondents (47,2%) had good sleep quality, while 103 respondents had poor sleep quality (52,8%). A total of 123 respondents (63,15) experiences Acne vulgaris. Chi-square statistical analysis using SPSS software showed a significant correlation between sleep quality and Acne vulgaris (p-value <0,05; PRR = 1,261; 95% CI = 1,261-1,576). Conclusion: Poor sleep quality can increase the risk of developing Acne vulgaris.